OP0054 Complete freund's adjuvant induces, in interferon-gamma-deficient mice, a chronic inflammatory disease reminiscent of systemic juvenile idiopathic arthritis. (23rd January 2014) - Avau, A.; Mitera, T.; Put, K.; Put, S.; Tousseyn, T.; Billiau, A.D.; Wouters, C.; Matthys, P.
Abstract : Background: Systemic juvenile idiopathic arthritis (sJIA) is a disease characterized by arthritis and systemic features such as fever, rash, lymphadenopathy and leukocytosis. The underlying pathogenic mechanism of sJIA is not understood but prolonged stimulation of immune cells and excessive production of cytokines are considered to be important in the pathogenesis of the disease. Objectives: The lack of a suitable animal model is a major drawback in the investigation of the pathogenesis of sJIA. We examined whether complete Freund's adjuvant (CFA), a widely used reagent for chronic stimulation of the immune system, can elicit sJIA-like features in mice. Since interferon-gamma (IFN-γ) exerts key functions in activating and regulating innate and adaptive immune responses and given the disputable role of IFN-γ in sJIA patients, we examined our hypothesis in wild type as well as IFN-γ-deficient mice. Methods: IFN-γ-deficient (IFN-γ KO) and wild type mice were injected s.c. with CFA. Body weight, clinical signs of arthritis, complete blood cell counts and peripheral blood biochemistry were monitored. Inflammatory cytokine levels were measured by qPCR and ELISA. Flow cytometry and histology were performed on spleen, liver, bone marrow and lymph nodes. Results: Consistent with the immune stimulating properties of CFA, both IFN-γ KO and wild type mice showed splenomegaly and lymphadenopathy from 10 days after CFA challenge onward. Both substrains also developed weight loss; however, while this was transient in wild type animals, it was prolonged and more severe in IFN-γ KO mice. Furthermore, a proportion of the IFN-γ KO, but not wild type mice developed skin rashes as well as redness and swelling in the joints, histologically consistent with prominent synovitis. Complete blood counts demonstrated an increase in platelets and neutrophils in both substrains of mice, the increase being more pronounced in IFN-γ KO mice. IL-6 serum levels were significantly elevated in CFA-challenged IFN-γ KO mice only. Interestingly, between 11 to 40 days post CFA injection, approximately 30% of IFN-γ KO mice developed cytopenia and anemia, as evident from their significantly decreased lymphocyte and red blood cell counts, and decreases in hemoglobin and hematocrit levels. Intriguingly, in CFA-challenged IFN-γ KO mice, bone marrow, spleen, liver and blood showed a prominent infiltration of macrophages, including increased numbers of hemophagocytic macrophages. Conclusions: Upon challenge with CFA, IFN-γ KO mice developed clinical, biological and pathological features similar to those seen in patients with sJIA. A proportion of these mice also developed severe inflammation with wasting, anemia and hemophagocytosis, features that are seen in a subset of sJIA patients, diagnosed with macrophage activation syndrome (MAS). To our knowledge, this is the first animal model of sJIA showing an association with MAS. Our data demonstrate that IFN-γ is not required for chronic anemia and hemophagocytosis and challenge the concept that IFN-γ is the critical driver of MAS. Disclosure of Interest: None Declared